THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT IN THE INNOVATIVE BEHAVIOR OF EMPLOYEES: AN ANALYTICAL SURVEY OF THE OPINIONS OF A SAMPLE OF CIVIL UNIVERSITY EMPLOYEES IN DHI QAR GOVERNORATE (World Bulletin of Management and Law, 2022)
The research aims to test the relationship between perceived organizational support in its dimensions (organizational commitment, organizational justice, participation in decision-making) and its impact on innovative behavior in its dimensions (idea generation, idea recreation, and idea implementation) for a sample of private university employees in Dhi Qar governorate, represented by ( Al Ain University, the National University of Science and Technology, and the Faculty of Mazaya University), where the questionnaire was distributed in an intentional sampling manner to (259) senior and middle administrative leaders and teachers working in the surveyed private universities, for the purpose of data collection, which is processed by relying on the statistical program (SPSS.V.26) and the statistical program (AMOS.V.26) for the purpose of describing and analyzing the research variables, testing the main and secondary hypotheses of the study, verifying their validity, and making recommendations and future proposals. The research reached a number of results, perhaps the most prominent of which is the presence of a positive impact of perceived organizational support on the innovative behavior of employees